2013
DOI: 10.1002/rcm.6718
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform ion cyclotron resonance mass spectrometric analysis of the green fraction of soil humic acids

Abstract: The important molecular formulae of Pg components were estimated utilizing FTICRMS. Copyright © 2013 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Sato (1976a), who examined the chemical property of Pg prepared by gel chromatography on Sephadex G-50, reported that a very small amount of DHPQ was isolated by sublimation of 10% (w/v) NaOH-insoluble fraction of Pg. As previously mentioned, Ikeya et al (2013) detected DHPQ and DHPQ substituted with carboxyl and/or hydroxyl groups and phenyl-DHPQ derivatives from FTICR-MS analysis of purified Pg. Other researchers have also suggested the presence of such acidic functional groups in Pg (Sato 1976a;Watanabe et al 1996).…”
Section: Chemical Properties Of Isolated Cegf Componentssupporting
confidence: 58%
See 3 more Smart Citations
“…Sato (1976a), who examined the chemical property of Pg prepared by gel chromatography on Sephadex G-50, reported that a very small amount of DHPQ was isolated by sublimation of 10% (w/v) NaOH-insoluble fraction of Pg. As previously mentioned, Ikeya et al (2013) detected DHPQ and DHPQ substituted with carboxyl and/or hydroxyl groups and phenyl-DHPQ derivatives from FTICR-MS analysis of purified Pg. Other researchers have also suggested the presence of such acidic functional groups in Pg (Sato 1976a;Watanabe et al 1996).…”
Section: Chemical Properties Of Isolated Cegf Componentssupporting
confidence: 58%
“…As mentioned earlier, Sato (1976a) indicated that the EtOAc-soluble fraction of Pg was only 6% in addition to a very small amount of DHPQ. Ikeya et al (2013) also reported that DHPQ and its derivative accounted for 4.6% and 23.6%, respectively, of the purified Pg component based on FTICR-MS analysis, though the quantitative performance of this method is still debatable (Sugiyama 2010). It is impossible to directly compare our data with theirs due to the differences in soil sample, extraction method and sample treatment.…”
Section: Relationship Between Cegf and Pgmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to characterize the chemical nature of the large molecular weight-absorbing species, the mass spectra of the compounds separated by SEC were measured. For the chemical speciation of organics in aerosols, electrospray ionization operated in negative mode (ESIÀ) is most commonly employed [Wozniak et al, 2008;Laskin et al, 2009Laskin et al, , 2014Smith et al, 2009;Leclair et al, 2012;Lin et al, 2012Lin et al, , 2014Ikeya et al, 2013;Nguyen et al, 2014]. The total absorbing feature was split into two sections according to the local absorbance maxima in the total ion current (TIC) as shown in Figure 2a.…”
Section: 1002/2015gl066954mentioning
confidence: 99%